2021
DOI: 10.21037/tcr-21-467
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of preoperative brachytherapy for controlling vaginal bleeding in early-stage cervical cancer: a retrospective study

Abstract: Background: In our clinical study, 11% of the patients with early-stage cervical cancers had different degrees of vaginal bleeding, which required a preoperative intervention. We set to assess the efficacy and safety of preoperative high-dose rate vaginal ovoid brachytherapy (HDR-VOBT) for the treatment of vaginal bleeding in women with early cervical cancer.Methods: We retrospectively identified and reviewed patients with vaginal bleeding and early-stage cervical carcinoma, treated between January 2011 and De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…These include initiating sexual activity under the age of 16 years, having multiple sexual partners and infrequent condom use, prolonged use (more than 5 years) of oral contraceptive pills, having a weakened immune system (including being HIV positive), low socioeconomic status, and smoking [13]. In addition to these risk factors, it is valid to note that some researchers reported a massive gap in knowledge about the risk factors in the general population [14,15], which may result in delayed diagnosis and treatment because women are unaware of how the disease presents itself [16] or whether they are at risk.…”
Section: Cervical Cancer -Risk Factors Prevention and Treatmentmentioning
confidence: 99%
See 3 more Smart Citations
“…These include initiating sexual activity under the age of 16 years, having multiple sexual partners and infrequent condom use, prolonged use (more than 5 years) of oral contraceptive pills, having a weakened immune system (including being HIV positive), low socioeconomic status, and smoking [13]. In addition to these risk factors, it is valid to note that some researchers reported a massive gap in knowledge about the risk factors in the general population [14,15], which may result in delayed diagnosis and treatment because women are unaware of how the disease presents itself [16] or whether they are at risk.…”
Section: Cervical Cancer -Risk Factors Prevention and Treatmentmentioning
confidence: 99%
“…Because the severity of pain increases as the development of cancer progresses, these women often reported experiencing pain in more than 2 areas of the body with an overall score of 4 on a pain scale of 0-5 (0 being no pain; 5 being severe pain) and required the administration of opioids. As time progressed, a consequent study that was conducted in 2021 revealed that vaginal bleeding was also commonly reported, with a high prevalence of 89% [16]. Although intermenstrual and post-coital bleedings are common symptoms of cervical cancer, they may also be associated with benign conditions such as polyps, uterine fibroids, ovulatory or endometrialrelated disorders, birth control, sexually transmitted infections, or trauma [22,23].…”
Section: Symptoms Of Cervical Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…At present, external irradiation combined with intracavitary posterior radiotherapy and concurrent chemotherapy is the standard method for the treatment of medium-term and advanced cervical cancer. Traditional radiotherapy methods such as four-field box-type and front-to-back penetrating irradiation have been used earlier and are widely used, but their damage to the digestive tract, urinary tract and hematopoietic systems is relatively serious ( 2 , 3 ). Intensity modulated radiation therapy (IMRT) and three dimensional conformal radiation therapy (3D-CRT) are new radiotherapy techniques, and there is no unified understanding on the specific effects of these two techniques.…”
Section: Introductionmentioning
confidence: 99%